After the Cold War : essays on the emerging world order - Lepor, Keith Philip, 1961- (University of Texas Press, 1997)
The end of the Cold War between the United States and the former Soviet Union reassured people around the world who had lived in fear of a nuclear confrontation between the superpowers. Yet the early euphoria over "peace dividends" and a "new world order" was premature. Conflicts within and between nation-states are springing up around the globe, challenging world leaders and ordinary citizens to find peaceful means for national, group, and individual self-determination. In this book of specially commissioned essays, twenty world leaders assess the possibilities and perils of the new strategic, political, and economic interrelationships that are emerging around the world. They tackle such fundamental questions as: What is the future of the international system as we approach the twenty-first century? What will be the fate of disintegrating nation-states, and how will the international community respond? Has the nation-state outlived its usefulness? Are we beginning to witness the complete breakdown of the international system? This book will be an invaluable tool for diplomats and politicians, scholars, and business leaders. General readers also will find here an excellent overview of the emerging world order, written by those who are currently shaping it.--Publisher description